Identidade entre as causas e os princípios na Metafísica de Aristóteles - Martins, Jonas de Pinho (2025)
This paper seeks to understand the relationship between the concepts of principle and cause in Aristotle's Metaphysics. We can argue that causes and principles are equivalent terms; especially when we consider certain passages in the Metaphysics, such as A2 (Met. 1. 982 a 28 - 30), A3 (Met. 1. 983 a 24 - 26), Γ2 (Met. 4. 1003 b 18), Γ2 (Met. 4. 1003 b 22 - 26), Δ1 (Met. 5. 1013 a 17) and Z17 (Met. 7. 1041 a 9 - 10), for example. Regarding the notions of cause and principle, this study is relevant given that these concepts have not been fully clarified, as they are sometimes used interchangeably in the literature. Regarding their identity, it is necessary to explicitly state when they are the same and when they are different. It is also important to evaluate the several meanings of these terms, such as the definitions of principle and cause in Book Δ and in other texts of the Metaphysics. Thus, this dissertation consists of a theoretical investigation, an analysis of the identity between the concepts of cause and principle proposed by Aristotle in Metaphysics. It follows, then, that "cause" and "principle" are equivalent, analogous to "Being" and "One", and that both terms present the same extension in the same scenario, such that they are convertible, as in "the cause of X being thus" and "the principle of X being thus", for example.